Transcriptome analysis reveals the sex-switching mechanism of juvenile hermaphroditism in silver pomfret (Pampus argenteus) - Yaya Li; Jiabao Hu; Chongyang Wang; Man Zhang; Youyi Zhang; Yuanbo Li; Mengke Tang; Chunlai Qin; Zukang Feng; Shanliang Xu; Xiaojun Yan; Xubo Wang; et al. (Biology of Sex Differences)
Abstract Background Our previous study on silver pomfret (Pampus argenteus) demonstrated that all gonads initially develop into ovaries by 60 days post-hatch (dph). Between 80 and 120 dph, some oocytes undergo apoptosis, resulting in the development of testes and a transient hermaphroditic stage. This observation indicates a complex molecular mechanism underlying sex differentiation in this species. Methods Gonadal samples were collected at 90 dph, 120 dph, and 150 dph, with sex identification performed by HE staining and transcriptome sequencing. Morphological traits, including body length and weight, were measured to evaluate sexual size dimorphism. Candidate genes related to with sex differentiation were identified through differential gene expression analysis and feature selection methods, followed by gene set enrichment analysis to identify potential molecular pathways. Heatmaps were generated to visualize gene expression patterns across developmental stages and samples. Sex hormones concentrations were measured using commercial assay kits to assess their role in gonadal differentiation. RT-qPCR validated the sequencing results, while immunofluorescence (IF) examined the expression of related genes in testes and ovaries. Results Histological and transcriptomic analyses identified the period between 90 and 120 dph as critical for sex differentiation in silver pomfret. At 90 dph, apoptotic signals trigger the apoptosis of early-stage oocytes. During this period, both testis-preferential and ovary-preferential genes exhibit high expression, leading to spermatogonia differentiation and the emergence of a juvenile hermaphroditic stage. The study established that androgens 11-KT and estrogen E2 regulate sex differentiation through modulation of related gene expression, with 11-KT serving a crucial role. This process involved significant enrichment of the steroid hormone biosynthesis pathway and the metabolism of xenobiotics by cytochrome P450 in the testes. Ovarian development is characterized by fatty acid metabolism and PPAR signaling pathway activation, along with energy metabolism pathways including the citrate cycle (TCA cycle) and cell degradation processes, such as lysosome activity and ubiquitin-mediated proteolysis, suggesting that ovarian development encompasses lipid accumulation and follicular selection. Conclusions This investigation illuminates the molecular processes underlying this distinctive pattern of gonadal differentiation, providing novel insights into sex differentiation in fish exhibiting a juvenile hermaphroditic stage. Graphical Abstract